The effect of the( T.A.S.C) model on the achievement of fifth-grade primary school students in science (Journal of the College of Basic Education, 2025)
The research aims to identify the impact of the T.A.S.C. model on the achievement of fifth-grade female students in science by verifying the validity of the following hypothesis: There is no statistically significant difference at a significance level of (0.05) between the average scores of students in the experimental group, who will study according to the T.A.S.C. model, and the average scores of students in the control group, who will study according to the traditional achievement method. The researchers adopted the experimental design with two experimental and control groups with partial control of the same post-test for achievement. The research community was determined as girls’ primary schools (daytime - governmental) in Babil Governorate for the academic year (2024-2025 AD). (Osama Bin Zaid Primary School for Girls) was chosen as a deliberate sample consisting of (88) students and distributed into two experimental groups, which numbered (43) students and a control group, which numbered (41) students. The two groups were equalized with the following variables: (the chronological age of the students calculated in months, the parents’ academic achievement, intelligence - Raven, the science principles subject grades for the first semester, and previous information). The experiment was conducted in the second semester of the academic year (2024-2025). (157) behavioral objectives and (32) study plans were prepared for each group, and an academic achievement test consisting of (40) paragraphs was prepared and achieved validity and reliability. Statistical methods were used: (Pearson coefficient and t-test Difficulty and discrimination coefficients, the effectiveness of false alternatives, the Kuder-Richardson-20 equation, and the Cohen-Spearman-Brown equation were used. After the experiment was completed, a science achievement test was administered. The results showed that the experimental group students outperformed the control group students on the achievement test. Based on this, conclusions, recommendations, and proposals were presented